Relatively Abusive and Relatively Corrupt: An Analytical Framework for the Study of Subtitlers' Visibilities - Huang, Boyi (The Journal of Specialised Translation, 2022)
This article attempts to interrogate the complexity of the current subtitling field through the lens of subtitler visibility. Currently, subtitlers adopt diverse subtitling approaches and emerge in various identities. Such multiplicity frustrates any binary and/or definitive preconceptions of subtitler visibility. Scholars have examined subtitlers' visibilities, however, rarely through subtitles, and more rarely in a systematic manner. This article aims to contribute to knowledge by developing a framework for analysing subtitlers' visibilities through their subtitles, i.e., for answering the question: how do different sets of subtitles give respective subtitlers different visibilities? Built on Nornes' (2007) notions of corrupt and abusive subtitling, it proposes a nonbinary, multimodal, and bidimensional comparative framework that contrasts subtitlers' visibilities as respectively manifested by their approaches towards the represented (non)verbal source and representing technical/verbal target of subtitling. It is argued that this novel framework enables a fuller capture of the dynamics of subtitlers' visibilities and, as such, it provides a systematic means to move beyond any binary and reductionist preconceptions of subtitler visibility.